Handloom industry in India - "Nambiar, A. C. K." (New Delhi, 1996)
Handloom industry is one of the oldest and biggest industries in the country. Given the right backing the industry can play a much more useful role in the economy and this fact has been well recognised since the era of planning in the country. Accordingly a number of policy measures were adopted to protect and develop the industry. How ever, the developmental impact of the mea sures were subject to considerable specu lation. This book based on a micro level study of handloom units at two points in time sheds much light on this aspect. After examining the structure and the question of growth of the industry the study comes to the startling conclusion that the industry is languishing. In the private sector the productive factors are subjected to intense exploitation and unable to withstand the exploitation the handloom units are wither ing away. Though the co-operative sector succeeded in protecting the interest of the labour under their fold the unfair practices of the private sector badly affects the com petitive strength of the co-operative sec tor. Unless remedial measures are taken to correct the malady the study notes that the handloom industry will become a relic of the past in the near future.
Keywords: Haandloom industries-India